The Role of Digitalization of Financial Inclusion in Reducing Income Gaps: an Empirical Study at 33 Provinces in Indonesia - Murtama, Abram Julion; Falianty, Telisa Aulia (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
One of the problems faced by developing countries, including Indonesia, is income inequality. It is hoped that digitalization of financial inclusion can solve this problem. Increasing financial inclusion is expected to make financial services more accessible to everyone, especially for poor groups who previously did not have access to financial services. This research aims to analyze the role of digitalization of financial inclusion in reducing income gaps using empirical evidence from 33 provinces in Indonesia during the 2013-2022 period, using the fixed effects estimation method. The results of this study indicate that financial inclusion has a negative and significant impact on the Williamson index. This means that increasing financial inclusion can reduce income inequality. The decomposition results for each dimension show that the access dimension has a significant effect on reducing income inequality in Indonesia, while the usage dimension shows a positive influence on income inequality, but the presence of the SNKI policy in Indonesia in 2016-2022 has a negative influence on income inequality in Indonesia.